Carbon dioxide

A C O X 2 \ce{CO_2} molecule consists of two oxygen atoms of mass m 1 = m 3 16 u m_1 = m_3 \approx 16 \, \text{u} and a carbon atom of mass m 2 12 u m_2 \approx 12 \, \text{u} . In order to model the electrostatic forces between the atoms, we imagine elastic springs with the force constant k k between the oxygen and the carbon. In equilibrium, the atoms each have a distance of d d from each other. The forces acting on the individual atoms result in F 1 = m 1 x ¨ 1 = k ( x 1 x 2 + d ) F 2 = m 2 x ¨ 2 = k ( x 2 x 1 d ) k ( x 2 x 3 + d ) F 3 = m 3 x ¨ 3 = k ( x 3 x 2 d ) \begin{aligned} F_1 = m_1 \ddot x_1 &= -k(x_1 - x_2 + d) \\ F_2 = m_2 \ddot x_2 &= -k(x_2 - x_1 - d) - k(x_2 - x_3 + d)\\ F_3 = m_3 \ddot x_3 &= -k(x_3 - x_2 - d) \end{aligned} along the x x -axis. We assume harmonic oscillations of the atoms: x 1 = ξ 1 e i ω t x 2 = ξ 2 e i ω t + d x 3 = ξ 3 e i ω t + 2 d \begin{aligned} x_1 &= \xi_1 e^{i\omega t} \\ x_2 &= \xi_2 e^{i\omega t} + d\\ x_3 &= \xi_3 e^{i\omega t} + 2d \end{aligned} with amplitudes ξ n \xi_n and frequency ω \omega . Show that there are only two possible solutions ω symmetric \omega_\text{symmetric} and ω asymmetric \omega_\text{asymmetric} for the frequency, that correspond to symmetric and asymmetric stretching vibrations, respectively.

What is the ratio α = ω asymmetric ω symmetric \displaystyle \alpha = \frac{\omega_\text{asymmetric}}{\omega_\text{symmetric}} of the frequencies?



Bonus question: What is the role of these vibrations for the greenhouse effect of carbon dioxide?


The answer is 1.915.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Markus Michelmann
Oct 17, 2017

Substituting x n = ξ n e i ω t + ( n 1 ) d x_n = \xi_n e^{i \omega t} + (n-1)d in the equations of motions results F 1 = m 1 ω 2 ξ 1 e i ω t = k ( ξ 1 ξ 2 ) e i ω t F 2 = m 2 ω 2 ξ 2 e i ω t = k ( 2 ξ 2 ξ 1 ξ 3 ) e i ω t F 3 = m 1 ω 2 ξ 3 e i ω t = k ( ξ 3 ξ 2 ) e i ω t \begin{aligned} F_1 = - m_1 \omega^2 \xi_1 e^{i \omega t} &= -k(\xi_1 - \xi_2)e^{i \omega t} \\ F_2 = - m_2 \omega^2 \xi_2 e^{i \omega t} &= -k(2 \xi_2 - \xi_1 - \xi_3)e^{i \omega t}\\ F_3 = - m_1 \omega^2 \xi_3 e^{i \omega t} &= -k(\xi_3 - \xi_2) e^{i \omega t} \end{aligned} This is set of linear equations for the displacement vector ( ξ 1 , ξ 2 , ξ 3 ) (\xi_1, \xi_2,\xi_3) . After dividing by e i ω t e^{i \omega t} and putting all terms to one side of the equation we get a homogeneous matrix equation ( k m 1 ω 2 k m 1 0 k m 2 2 k m 2 ω 2 k m 2 0 k m 1 k m 1 ω 2 ) ( ξ 1 ξ 2 ξ 3 ) = 0 \left( \begin{array}{ccc} \frac{k}{m_1} - \omega^2 & -\frac{k}{m_1} & 0 \\ -\frac{k}{m_2} & \frac{2k}{m_2} - \omega^2 & -\frac{k}{m_2} \\ 0 & -\frac{k}{m_1} & \frac{k}{m_1} - \omega^2 \end{array}\right) \left( \begin{array}{c} \xi_1 \\ \xi_2 \\ \xi_3 \end{array} \right) = 0 This equation has a nontrivial solution ξ n 0 \xi_n \not= 0 , only if the determinant of the matrix equals zero: 0 = k m 1 ω 2 k m 1 0 k m 2 2 k m 2 ω 2 k m 2 0 k m 1 k m 1 ω 2 = ( k m 1 ω 2 ) 2 ( 2 k m 2 ω 2 ) 2 k 2 m 1 m 2 ( k m 1 ω 2 ) = ( k m 1 ω 2 ) [ ( k m 1 ω 2 ) ( 2 k m 2 ω 2 ) 2 k 2 m 1 m 2 ] = ( k m 1 ω 2 ) ( ω 2 ( k m 1 + 2 k m 2 ) ) ω 2 \begin{aligned} 0 &= \left| \begin{array}{ccc} \frac{k}{m_1} - \omega^2 & -\frac{k}{m_1} & 0 \\ -\frac{k}{m_2} & \frac{2k}{m_2} - \omega^2 & -\frac{k}{m_2} \\ 0 & -\frac{k}{m_1} & \frac{k}{m_1} - \omega^2 \end{array}\right| \\ &= \left(\frac{k}{m_1} - \omega^2\right)^2 \left(\frac{2k}{m_2} - \omega^2\right) - 2 \frac{k^2}{m_1 m_2} \left(\frac{k}{m_1} - \omega^2\right) \\ &= \left(\frac{k}{m_1} - \omega^2\right) \left[ \left(\frac{k}{m_1} - \omega^2\right) \left(\frac{2k}{m_2} - \omega^2\right) -2 \frac{k^2}{m_1 m_2} \right]\\ &= \left(\frac{k}{m_1} - \omega^2\right) \left( \omega^2 - \left(\frac{k}{m_1} + \frac{2k}{m_2}\right) \right) \omega^2 \end{aligned} The solution ω = 0 \omega = 0 corresponds to a rigid movement of the whole molecule. Therefore, there are only to relevant zeros, that corresponds to natural frequencies of the molecule ω 1 = k m 1 , ω 2 = k m 1 + 2 k m 2 \omega_1 = \sqrt{\frac{k}{m_1}}, \quad \omega_2 = \sqrt{\frac{k}{m_1} + \frac{2k}{m_2}} Substituting ω = ω 1 \omega = \omega_1 in the matrix equation, we get ( 0 k m 1 0 k m 2 2 k m 2 k m 1 k m 2 0 k m 1 0 ) ( ξ 1 ξ 2 ξ 3 ) = 0 ( ξ 1 ξ 2 ξ 3 ) = ( ξ 1 0 ξ 1 ) \left( \begin{array}{ccc} 0 & -\frac{k}{m_1} & 0 \\ -\frac{k}{m_2} & \frac{2k}{m_2} - \frac{k}{m_1} & -\frac{k}{m_2} \\ 0 & -\frac{k}{m_1} & 0 \end{array}\right) \left( \begin{array}{c} \xi_1 \\ \xi_2 \\ \xi_3 \end{array} \right) = 0 \quad \Rightarrow \quad \left( \begin{array}{c} \xi_1 \\ \xi_2 \\ \xi_3 \end{array} \right) = \left( \begin{array}{c} \xi_1 \\ 0 \\ -\xi_1 \end{array} \right) Therefore, we have a symmetric vibration with $\omega 1 = \omega \text{symmetric}$. For the case ω = ω 2 = ω asymmetric \omega = \omega_2 = \omega_\text{asymmetric} it follows ( 2 k m 2 k m 1 0 k m 2 k m 1 k m 2 0 k m 1 2 k m 2 ) ( ξ 1 ξ 2 ξ 3 ) = 0 ( ξ 1 ξ 2 ξ 3 ) = ( ξ 1 2 μ ξ 1 ξ 1 ) \left( \begin{array}{ccc} \frac{2 k}{m_2} & -\frac{k}{m_1} & 0 \\ -\frac{k}{m_2} & \frac{k}{m_1} & -\frac{k}{m_2} \\ 0 & -\frac{k}{m_1} & \frac{2 k}{m_2} \end{array}\right) \left( \begin{array}{c} \xi_1 \\ \xi_2 \\ \xi_3 \end{array} \right) = 0 \quad \Rightarrow \quad \left( \begin{array}{c} \xi_1 \\ \xi_2 \\ \xi_3 \end{array} \right) = \left( \begin{array}{c} \xi_1 \\ -2\mu \xi_1 \\ \xi_1 \end{array} \right) with μ = m 1 / m 2 \mu = m_1/m_2 , so that the results corresponds to the asymmetric vibration. Finally, the frequency ratio results α = ω 2 ω 1 = 1 + 2 m 1 m 2 1 + 8 3 1.915 \alpha = \frac{\omega_2}{\omega_1} = \sqrt{1 + \frac{2 m_1}{m_2}} \approx \sqrt{1 + \frac{8}{3}} \approx 1.915

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...